Cloning, Identification and Functional Characterization of Bovine Free Fatty Acid Receptor-1 (FFAR1/GPR40) in Neutrophils - Manosalva, Carolina (PLoS One, 2015)
Long chain fatty acids (LCFAs), which are ligands for the G-protein coupled receptor FFAR1 (GPR40), are increased in cow plasma after parturition, a period in which they are highly susceptible to infectious diseases. This study identified and analyzed the functional role of the FFAR1 receptor in bovine neutrophils, the first line of host defense against infectious agents. We cloned the putative FFAR1 receptor from bovine neutrophils and analyzed the sequence to construct a homology model. Our results revealed that the sequence of bovine FFAR1 shares 84% identity with human FFAR1 and 31% with human FFAR3/GPR41. Therefore, we constructed a homology model of bovine FFAR1 using human as the template. Expression of the bovine FFAR1 receptor in Chinese hamster ovary (CHO)-K1 cells increased the levels of intracellular calcium induced by the LCFAs, oleic acid (OA) and linoleic acid (LA); no increase in calcium mobilization was observed in the presence of the short chain fatty acid propionic acid. Additionally, the synthetic agonist GW9508 increased intracellular calcium in CHO-K1/bFFAR1 cells. OA and LA increased intracellular calcium in bovine neutrophils. Furthermore, GW1100 (antagonist of FFAR1) and U73122 (phospholipase C (PLC) inhibitor) reduced FFAR1 ligand-induced intracellular calcium in CHO-K1/bFFAR1 cells and neutrophils. Additionally, inhibition of FFAR1, PLC and PKC reduced the FFAR1 ligand-induced release of matrix metalloproteinase (MMP)-9 granules and reactive oxygen species (ROS) production. Thus, we identified the bovine FFAR1 receptor and demonstrate a functional role for this receptor in neutrophils activated with oleic or linoleic acid.